Extracellular vesicle microRNA cargo is correlated with HPV status in oropharyngeal carcinoma. (10th October 2018) - Peacock, Ben; Rigby, Alice; Bradford, James; Pink, Ryan; Hunter, Keith; Lambert, Daniel; Hunt, Stuart
Abstract : Background: The incidence of human papilloma virus positive (HPV + ) oropharyngeal squamous cell carcinoma (OPSCC) has increased rapidly in recent decades. These tumours have a favourable outcome compared to HPV‐negative (HPV − ) OPSCC. However, HPV + tumours are more likely to metastasise to distant sites, suggesting a difference in how these tumour subtypes interact with the metastatic niche. Extracellular vesicles (EVs) have emerged as important players in cell‐to‐cell communication and are a potential source of biomarkers for cancer diagnosis. This study aims to characterise the microRNA cargo of small EVs released by HPV + and HPV − OPSCC cell lines. Methods: Extracellular vesicles produced by HPV + (SCC2 and SCC90) and HPV − (SCC72 an SCC89) OPSCC cells were characterised by tunable resistive pulse sensing (TRPS) and western blotting. RNA was extracted from EVs and analysed by small RNA sequencing. A bioinformatics approach was used to identify EV miRNA signatures associated with HPV status. Results: HPV − OPSCC cells produced more EVs than HPV + OPSCC cells. EVs were positive for the common EV markers CD63, CD9 and TSG101. Unbiased hierarchical clustering analysis of EV miRNA cargo revealed that samples clustered based on HPV status. 14 miRNA were enriched in HPV + cell‐derived EVs, whereas 19 miRNA were enriched in EVs derived from HPV − cell lines. Conclusions: Here, we identify EV miRNA signatures indicative of the HPV status of the parent cell. This may provide a platform from which to validate salivary or blood‐based biomarkers with utility for early detection and stratifying risk in OPSCC patients.